Investigation of the interaction between polymer and surfactant aqueous solution for the petroleum industry. (16th February 2017) - Nagy, R.; Bartha, L.; Tóth, J.; Dudás, J.; Vágó, Á.
ABSTRACT: The interactions between polymers and surfactants have been extensively studied. This is particularly important for understanding the mechanism of chemical enhanced oil recovery. The interaction between different surfactant mixtures and the flow modifier type HPAM (partially hydrolyzed polyacrylamide) polymer in water solutions was analyzed by different methods. Based on the experimental data a significant level of interaction between the surfactants and the HPAM polymer were found. It was obtained that by applying flow modifier polymer together with the own developed surfactants the additional oil production could increase.